Dissolved load, chemical weathering, and CO2 uptake dynamics of small tropical mountainous rivers of Southern Granulite Terrain, Karamana and Vamanpuram, Western Ghats, India - B. Upendra; M. Ciba; S. Rahul; G. Sreenivasulu; S. Kiran Kumar Reddy; V. Arun; K. Anoop Krishnan (Scientific Reports)
Abstract Chemical weathering in a river basin is a key geochemical process that controls fluxes between the atmosphere, land, and ocean, playing a crucial role in regulating Earth’s climate, particularly the small tropical mountainous rivers with high weathering yield. This study delves into the dissolved solute chemistry of two small tropical mountainous rivers in India’s Southern Granulite Terrain (SGT): the Karamana River Basin (KRB) and Vamanapuram River Basin (VRB), together referred as KVRB. Seventy-two water samples (36 per river) that are collected across three seasons are analysed for various physio-chemical parameters using standard methods. A chemical mass balance (CMB) model was employed to quantify solute sources, while silicate weathering rates (SWR), and CO2 consumption rates (CCR) were estimated separately. Results show that silicate weathering is the dominant process, followed by anthropogenic and atmospheric contributions, particularly at the river outlets. At the KRB outlet, SWR is 30.96 t km⁻² yr⁻¹, and CCR is 1.16 × 10⁶ mol km⁻² yr⁻¹, whereas VRB shows lesser values of 22.89 t km⁻² yr⁻¹ and 3.20 × 10⁵ mol km⁻² yr⁻¹. The lower Arrhenius activation energies of 27 kJ mol⁻¹ for KRB and 25 kJ mol⁻¹ for VRB are evident for intense silicate weathering Additionally, the physical weathering rates (PWR), evaluated using total suspended solids (TSS) concentrations, are more significant in KRB, particularly during the monsoon, due to it’s steep terrain and humid climate; while VRB experiences less physical weathering. The study emphasizes the complex interaction of silicate and physical weathering processes with climate and geomorphological conditions of KVRB.